Investment Decisions of Generations Y and Z With Financial Literacy as a Moderation Variable in the Era of Digitalization - Mia Muchia Desda; Mai Yuliza; Satriadi Satriadi; Rika Desiyanti; Valen Febianni; Dini Dini (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Digital investment platforms have made various investment instruments increasingly accessible to younger generations in Indonesia, yet concerns persist about how financial literacy levels impact investment decision-making. This study aims to analyze the influence of financial literacy on investment decisions among Generation Y (millennials) and Generation Z in Indonesia, with financial literacy serving as a moderating variable. The research employed a quantitative approach through a survey of 300 respondents from both generations. Analysis of the data revealed that financial literacy significantly influenced investment decisions, with individuals possessing higher financial literacy demonstrating more measured and information-based investment choices compared to those with lower literacy levels. These findings have important implications for financial institutions, policymakers, and educational institutions in developing targeted financial education programs and risk management strategies for young investors. Based on these findings, this study recommends strengthening financial education initiatives for Generations Y and Z to promote more rational investment decision-making in the digital era.